Irenes ausentes : um estudo sobre a baixa representatividade do idoso gay - Flores, Cristiano da Costa (2019)
Introduction: Homosexual representation is built through visibility by establishing signs that make up the imaginary. Institutions, morality, and society establish heterosexuality as a rule, being those that transgress individuals that make up social minorities. The representativeness, as food of the imaginary, has fundamental importance so that the members of said minorities find their peers and construct like existing beings. The imagery of the young gay man in relation to aging is a portrait of a time and assesses the representativeness of the elderly gay man in society. Objective: To know the perception of homosexual men about aging and representativeness Method: Qualitative paradigm study of the descriptive-interpretative type, carried out through seven semi-structured interviews with individuals who identify themselves as homosexual men. Data were grouped into categories. Analysis and discussion of the data: The collected testimonies made possible the problematization of the lack of representativeness in categories based on the absence of models of gay old age, the fear of solitude, the difficulty of imagining the elderly, the absence of an easily accessible gay man reference and the self-perception of the impacts of the representative crisis. It is possible to problematize the low representativeness of homosexual elderly men and their impact on the imaginary of young gays in relation to the process of aging and old age. The low coexistence of young gay men with gay elders demonstrates their low representativeness in social bonds and in the media, in addition to the presence of the stigma of lonely aging. Final considerations: The lack of representativeness of active and successful aging elderly genders seems to feed the stereotype and discourse favorable to aging as a derogatory factor of social isolation.